(untitled) (Journal of Hama University, 2019)
The research aimed to identifying the difficulties of students in the learning of mathematical concepts from the teachers ,points of view, and the number of members of the research sample was (200) who were chosen at random. The researcher prepared a questionnaire of opinions commensurate with the questions of the research and its hypotheses of the research and it has applied on the research samples after verifying of its psychometric characteristics. The research concluded the following results: 1- The are statistical significant differences between the average scores of teachers on the questionnaire according to the variable of scientific qualification. 2- The are statistical significant differences between the average scores of teachers on the questionnaire according to the variable years of experienc